2021
DOI: 10.1038/s41598-021-86557-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coronavirus lockdowns on the ambient seismic noise levels in Gujarat, northwest India

Abstract: The Covid-19 pandemic created havoc and forced lockdowns in almost all the countries worldwide, to inhibit social spreading. In India as well, as a precautionary measure, complete and partial lockdowns were announced in phases during March 25 to May 31, 2020. The restricted human activities led to a drastic reduction in seismic background noise in the high frequency range of 1–20 Hz, representative of cultural noise. In this study, we analyse the effect of anthropogenic activity on the Earth vibrations, utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Schippkus et al (2020) used the large-N arrays in the Vienna Basin to collect environmental noise signals and analyzed the characteristics of urban environmental noise, including the railway track, windmills and oil pumpjacks. Through the ambient noise analysis, researchers monitored the changes of the urban traffic and human activities during the lockdown due to COVID-19 pandemic (Lecocq et al 2020;Roy et al 2021;Kuponiyi et al 2021). Monitoring traffic activity can also provide information for urban construction and management (e.g., Li et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Schippkus et al (2020) used the large-N arrays in the Vienna Basin to collect environmental noise signals and analyzed the characteristics of urban environmental noise, including the railway track, windmills and oil pumpjacks. Through the ambient noise analysis, researchers monitored the changes of the urban traffic and human activities during the lockdown due to COVID-19 pandemic (Lecocq et al 2020;Roy et al 2021;Kuponiyi et al 2021). Monitoring traffic activity can also provide information for urban construction and management (e.g., Li et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that during the COVID-19 lockdown there was decrease in noise levels due to the reduction of humanrelated activities, and as recorded by both broadband (Poli et al, 2020;Xiao et al, 2020;Lecocq et al, 2020;Somala, 2020;Dias et al, 2020;Roy et al, 2021;Grecu et al, 2021;Cannata et al, 2021) and strong motion (Yabe et al, 2020;Łukasz Ścisło et al, 2021) stations. These activities were affecting our stations more significantly since several of the RAN stations are located inside or near to the public buildings.…”
Section: Covid-19 Lockdownmentioning
confidence: 94%
“…In these countries, the government adopted a strict lockdown with a total ban on all non-essential movements. Wherever it has been adopted, this measure caused a net reduction of the seismic noise (e.g., Xiao et al [11], Yabe et al [14], Roy et al [16]) including the countries considered here [13,18]. Thus, for each one of the three countries we consider the earthquakes occurred in a time period across the adoption of the lockdown decree.…”
Section: Methodsmentioning
confidence: 99%
“…After the emergency of the COVID-19, many governments worldwide have adopted some restrictions that, in most cases, caused the reduction of anthropogenic noise. In princi-ple, this reduction implies the increase in the detection capability of smaller events [11][12][13][14][15][16] and, in turn, a net decrease of m c would be expected. However, to our knowledge, the greater part of papers focused on the noise analysis and on the improvement of earthquakes detectability.…”
Section: Introductionmentioning
confidence: 99%